(untitled) (Indian Journal of Public Health Research & Development, 2020)
Waste collectors usually expose to several occupational health and safety risks which may affect their health and wellbeing. Health literacy might help reducing occupational harms. Our aims were to assess the health statusand to determine the influence of health literacy (HL) and occupational health and safety (OHS) factors on quality of life (QOL) of local administration organization waste collectors in Thailand. This cross-sectional study was conducted among 529 participants who were recruited by using a multistage random sampling from local administration organizations in 4 provinces of the Northeast of Thailand. A selfadministered structured questionnaire was used to assess OHS factors, HL, socioeconomic status (SES) and QOL. The Generalized Linear Mixed Model (GLMM) was used to determine the association between OHS, HL and QOL when controlling for other covariates. 62.95% of the participants reports as had good health status. However, 51.04% had musculoskeletal disorders (MSDs), 36.37% had work related injuries and 20.04% had chronic disease. Only 42.53% had adequate to excellence level of HL and the same proportion had good QOL. The GLMM analysis indicated factors that were significantly associated with good quality of life when controlling the effect of regions of municipal waste collectors in the Northeast of Thailand were: did not have MSDs, had adequate to excellence levels of health literacy, had low level of stress related with social support on work, had higher level of education, had high level of knowledge on garbage collection work, had low stress related with job security. Less than half of municipal waste collection workers had good QOL. HL, free from MSDs, knowledge about waste collection, low levels of stress on job security, and social support on job had influence on QOL as well as educational attainment.